Pharmacokinetics of furosemide administered 4 and 24 hours prior to high‐speed exercise in horses. Issue 2 (22nd October 2017) - Knych, H. K.; Vale, A.; Wilson, W. D.; Kass, P. H.; Arthur, R. M.; Jones, J. H.
Abstract : Furosemide is a diuretic agent used commonly in racehorses to attenuate the bleeding associated with exercise‐induced pulmonary hemorrhage (EIPH). The current study describes serum and urine concentrations and the pharmacokinetics of furosemide following administration at 4 and 24 hrs prior to maximal exercise. Eight exercised adult Thoroughbred horses received a single IV administration of 250 mg of furosemide at 4 and 24 hrs prior to maximal exercise on a high‐speed treadmill. Blood and urine samples were collected at time 0 and at various times for up to 72 hrs and furosemide concentrations determined using liquid chromatography–tandem mass spectrometry. Serum furosemide concentrations remained above the LOQ (0.05 ng/ml) for 36 hrs in 3/8 and 1/8 horses in the 4‐ and 24‐hrs groups, respectively. Serum concentration data were best fit by a two‐compartment model. There was not a significant difference in the volume of distribution at steady‐state (0.594 ± 0.178 [4 hrs] and 0.648 ± 0.147 [24 hrs] L/kg) or systemic clearance (0.541 ± 0.094 [4 hrs] and 0.617 ± 0.114 [24 hrs] L/hrs/kg) between horses that were exercised at 4‐ and 24 hrs postdrug administration. The mean ± SD elimination half‐life was 3.12 ± 0.387 and 3.23 ± 0.407 hrs following administration at 4 and 24 hrs prior to exercise, respectively.